The first 100 years of the Radon transform. (11th July 2018) - Ramlau, Ronny; Scherzer, Otmar
Abstract: This special issue is honoring the 100th anniversary of the publication of the famous paper by Johann Radon (1917 Ber. über Verh. Königlich-Sächsischen Ges. Wiss. Leipzig 69 262–77).